Laboratory course on fundamentals of nuclear physics study aid учебно-методическое пособие - Ryzhakova (Rizhakova) Physicist Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences; Rogova Physicist Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences; Verkhoturova linguist Head of the Department of Tomsk Polytechnic University, Candidate of historical sciences; Cherepennikov physicist Associate Professor of Tomsk Polytechnic University, Candidate of Sciences (TPU Publishing House, 2022)
The study guide presents 8 laboratory works on the course "Fundamentals of Nuclear Physics". The main attention is paid to issues of wide applied significance - radioactivity, interaction of radiation with matter, and nuclear physics methods of analysis. The principles and methods of ?- and ?-spectrometry and fundamentals of neutron activation analysis are considered. The guide is intended for students studying in the directions 14.03.02, 14.04.02 "Nuclear physics and technologies", 14.05.02 "Nuclear power plants: design, operation and engineering", 14.05.04 "Electronics and automation of physics installations".